2018
DOI: 10.2478/bjmg-2018-0026
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of circulating serum microRNA-328-3p and microRNA-3135a expression as promising novel biomarkers for autism spectrum disorder

Abstract: Circulating microRNAs (miRNAs) are emerging as promising diagnostic biomarkers for autism spectrum disorder (ASD), but their usefulness for detecting ASD remains unclear. Nowadays, development of promising biomarkers for ASD remains a challenge. Recently, dysregulation of the miRNAs expression in postmortem brain tissue, serum and peripheral blood, have been associated with ASD. Circulating miRNAs are known to be secreted by a number of different cells and can interpose delivery of information into receiver ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…Although the research on ASD is progressively and exponentially growing, only 8 papers have explored the use of circulating miRNAs (ci-miRNAs) in biofluids (Table 1) such as in serum (Vasu et al, 2014; Cirnigliaro et al, 2017; Kichukova et al, 2017; Popov et al, 2018; Yu et al, 2018) and in saliva (Hicks et al, 2016, 2018, 2019; Figure 3). Moreover, from the few investigations, only the three studies performed using saliva specimens incorporated a high-throughput approach (RNA-seq).…”
Section: Ci-mirnas As Predictive Biomarkers In Asdmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the research on ASD is progressively and exponentially growing, only 8 papers have explored the use of circulating miRNAs (ci-miRNAs) in biofluids (Table 1) such as in serum (Vasu et al, 2014; Cirnigliaro et al, 2017; Kichukova et al, 2017; Popov et al, 2018; Yu et al, 2018) and in saliva (Hicks et al, 2016, 2018, 2019; Figure 3). Moreover, from the few investigations, only the three studies performed using saliva specimens incorporated a high-throughput approach (RNA-seq).…”
Section: Ci-mirnas As Predictive Biomarkers In Asdmentioning
confidence: 99%
“…The study of Popov et al (2018), showed differential expression changes of miR-3135a and miR-328-3p in the serum of ASD individuals using qRT-PCR technology. Remarkably these miRNAs were previously described to play a role in the etiopathogenesis of several neurological disorders (Provost, 2010; De Felice et al, 2012).…”
Section: Ci-mirnas In Serum As Asd Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, this miRNA has been confirmed to dysregulate expression across the different brain tissue regions in AD patients (Puthiyedth et al, 2016). Hsa-mir-328 has been reported to be associated with a variety of neurologic disorders, such as autism spectrum disorder, Huntington's, Parkinson's, and Alzheimer's, and the biological functions of its targeting genes APP and BACE1 were validated experimentally in mouse brain tissues (Boissonneault et al, 2009;Provost, 2010;Nt et al, 2018). High-throughput experimental data from starBase were used to verify the results, and similar conclusions were obtained (see Supplementary Text S1 and Supplementary Table S7).…”
Section: Discussionmentioning
confidence: 97%
“…Numerous studies have shown that miRNAs affect cellular pathways and biological processes (Kim and Nam, 2006;Ragusa et al, 2017;O'Brien et al, 2018;Treiber et al, 2019), also playing an essential role in many aspects of neural development (e.g., neurogenesis, neuronal differentiation, maturation, synaptogenesis, neuronal plasticity, neuronal apoptosis) (Bian and Sun, 2011). Furthermore, miRNAs show specific expression and spatiotemporal patterns in mammalian central nervous systems (CNS) (Kosik, 2006;Rao et al, 2013); alterations of miRNA expression have been associated with various brain anomalies and neuropsychiatric disorders (Xu et al, 2010(Xu et al, , 2012Mundalil Vasu et al, 2014;Wu et al, 2015;Hicks et al, , 2019Alural et al, 2017;Cirnigliaro et al, 2017;Kichukova et al, 2017;Nt et al, 2018;Zadehbagheri et al, 2019), delineating a discriminative molecular signature (Salta and De Strooper, 2012). Furthermore, the evidence that extracellular RNA can be detected in all mammalian body fluids, including peripheral blood (Kosaka et al, 2010;Turchinovich et al, 2011Turchinovich et al, , 2013, opened the way to an important source of biomarkers (Rao et al, 2013;Kichukova et al, 2015;Rizzo et al, 2015): this finding revealed the possibility to analyze the expression of circulating miRNAs (cmiRNAs) through liquid biopsies, in a minimally invasive way (Rao et al, 2013;Nevel et al, 2018).…”
Section: Introductionmentioning
confidence: 99%